Time pieces : a Dublin memoir - Banville, John (Alfred A. Knopf, 2018)
Presents a memoir of the author's life near Dublin, a city that inspired his imagination and literary life and served as a backdrop for the dissatisfactions of adult years shaped by Dublin's cultural, political, architectural, and social history.